Using Network Science to Understand the Aging Lexicon: Linking Individuals' Experience, Semantic Networks, and Cognitive Performance. (18th January 2022) - Wulff, Dirk U.; De Deyne, Simon; Aeschbach, Samuel; Mata, Rui
Abstract: People undergo many idiosyncratic experiences throughout their lives that may contribute to individual differences in the size and structure of their knowledge representations. Ultimately, these can have important implications for individuals' cognitive performance. We review evidence that suggests a relationship between individual experiences, the size and structure of semantic representations, as well as individual and age differences in cognitive performance. We conclude that the extent to which experience‐dependent changes in semantic representations contribute to individual differences in cognitive aging remains unclear. To help fill this gap, we outline an empirical agenda that utilizes network analysis and involves the concurrent assessment of large‐scale semantic networks and cognitive performance in younger and older adults. We present preliminary data to establish the feasibility and limitations of such empirical, network‐analytical approaches. Abstract : Whether it is possible to define a rational standard in decision making and, if yes, whether such a standard is achievable by finite agents (such as humans) has been a hotly debated issue. This special issue offers an overview of some promising modern approaches to these questions, taking advantage of the latest developments in decision theory. We review evidence that suggests links between individual experiences, semantic representations, and age differences in cognitive performance, and present an empirical agenda and pilot data involving the assessment of large‐scale, individual semantic networks.